2004
DOI: 10.1016/j.ijdevneu.2004.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of the neuronal nitric oxide synthase expression in the superficial layers of the adult rat superior colliculus after perinatal enucleation

Abstract: The level of expression of the neuronal nitric oxide synthase (nNOS) in the retinorecipient layers of rat superior colliculus (SC) was investigated in adult rats after neonatal enucleation using two biochemical methods: (1) measurement of the in vitro specific-activity of NOS by the conversion of [3H]-arginine to [3H]-citrulline and (2) immunochemical analysis by western blotting and densitometry of immunoreactive bands using antibodies that recognise the three prominent isoforms of nNOS, alpha, beta and gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…There are, however, reports on nNOS down‐regulation after monocular enucleation in the rat (Batista et al, 2003; Zhang et al, 1996), and visual deprivation (Aoki et al, 1993) or inhibition of retinal activity (Wong‐Riley et al, 1998) in primates. In addition, de Bittencourt‐Navarrete et al (2004) have shown that unilateral enucleation does not change the total amount or the activity of nNOS in the SC, but only its distribution within neurons. There is apparently no simple explanation for these discrepant findings, although different ages, different species, and different protocols are some of the possible reasons subjacent to those different findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are, however, reports on nNOS down‐regulation after monocular enucleation in the rat (Batista et al, 2003; Zhang et al, 1996), and visual deprivation (Aoki et al, 1993) or inhibition of retinal activity (Wong‐Riley et al, 1998) in primates. In addition, de Bittencourt‐Navarrete et al (2004) have shown that unilateral enucleation does not change the total amount or the activity of nNOS in the SC, but only its distribution within neurons. There is apparently no simple explanation for these discrepant findings, although different ages, different species, and different protocols are some of the possible reasons subjacent to those different findings.…”
Section: Discussionmentioning
confidence: 99%
“…The present study involved only adult rats, and the results therefore reveal a marked plasticity of the nitrinergic system even in the adult stage. Other rat studies employed Lister (Batista et al, 2003; de Bittencourt‐Navarrete et al, 2004) or Long‐Evans (Nucci et al, 2000; Zhang et al, 1996) strains, but most of those experiments have also been conducted in newborn or young animals. The possibility of age playing a major role in those apparently discrepant findings is supported by the data from two different studies in the same species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that lack of neural activity produces changes in the intracellular distribution of nNOS in neurons of the SC (17,18). Despite the results of Zhang and co-workers (14) showing that eye removal causes a down-regulation of NADPH-d-positive neurons in the SC, the expression level of the different NADPH-d transcripts seems to be independent of such activity (19).…”
Section: Introductionmentioning
confidence: 99%